Problematika Pendaftaran Partai Politik Peserta Pemilu di Era Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum - Faizi Zain; Udiyo Basuki (Wacana Hukum, 2019)
The birth of Law Number 7 of 2017 concerning Elections strengthens the position of the Election Supervisory Body in enforcing election law. In addition to election crimes, other powers he has are taking action and deciding administrative violations, even though the authority is the authority of the State Administrative Court. This study is a combination of library research (library research) and field research (field research) that are descriptive analytical. The approach used is a normative approach. This study attempts to answer two questions; how to settle the election dispute process, and how the electoral dispute law enforcement system in Indonesia. The results showed that the authority to decide on dispute resolution in the electoral process was in Bawaslu whose decision was final and binding, but in practice legal remedies were made to the Administrative Court of Negarab and ended at the Supreme Court through appeals, appeals and judicial review.